2015
DOI: 10.1111/jmg.12134
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria modelling of blueschist and eclogite from the Sanbagawa metamorphic belt of southwest Japan reveals along‐strike consistency in tectonothermal architecture

Abstract: The Sanbagawa metamorphic belt of southwest Japan is one of the type localities of subductionrelated high-P metamorphism. However, variable pressure-temperature (P-T) paths and metabasic assemblages have been reported for eclogite units in the region, leading to uncertainty about the subduction zone paleo-thermal structure and associated tectonometamorphic conditions. To analyse this variation, phase equilibria modelling was applied to the three main high-P metabasic rock types documented in the regionglaucoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
1
22
2
Order By: Relevance
“…Amphibole compositional zoning is expected to evolve to glaucophane if the retrograde P–T path experiences significant cooling, however, the observed amphibole zoning in eclogite D205 (calcic cores to sodic‐calcic rims; Figure and Table ) indicate that the eclogite experienced high enough temperatures during exhumation to be in the calcic amphibole stability field (e.g., Forneris & Holloway, ; Weller, Wallis, Aoya, & Nagaya, ; Wei et al., ; Wilke, O'Brien, & Altenberger, ). Our results indicate that the Dulan eclogites experienced a retrograde P–T path to temperatures of ~580–660°C, enough to obliterate any evidence of lawsonite, but cold enough to preclude partial melting (Figures d, d, and c; Clarke et al., ; Wei & Clarke, ).…”
Section: Discussionmentioning
confidence: 99%
“…Amphibole compositional zoning is expected to evolve to glaucophane if the retrograde P–T path experiences significant cooling, however, the observed amphibole zoning in eclogite D205 (calcic cores to sodic‐calcic rims; Figure and Table ) indicate that the eclogite experienced high enough temperatures during exhumation to be in the calcic amphibole stability field (e.g., Forneris & Holloway, ; Weller, Wallis, Aoya, & Nagaya, ; Wei et al., ; Wilke, O'Brien, & Altenberger, ). Our results indicate that the Dulan eclogites experienced a retrograde P–T path to temperatures of ~580–660°C, enough to obliterate any evidence of lawsonite, but cold enough to preclude partial melting (Figures d, d, and c; Clarke et al., ; Wei & Clarke, ).…”
Section: Discussionmentioning
confidence: 99%
“…Whole‐rock major element compositions of quartz eclogites and mafic clots from the Gongen area and other lithologies of the Sanbagawa metamorphic belt. Data sources are as follows: Quartz eclogite and mafic clot (Miyamoto et al, ; Utsunomiya et al, ; Yokoyama, unpublished data; this study), metabasalt and metagabbro (Aoya et al, ; Banno, ; Endo et al, ; Ernst, Seki, Onuki, & Gilbert, ; Goto & Banno, ; Nozaki et al, ; Okamoto et al, ; Utsunomiya et al, ; Weller, Wallis, Aoya, & Nagaya, ; Enami, Iwata, and Yokoyama, unpublished data), metasediments (Aoya et al, ; Banno, ; Ernst et al, ; Fujiwara, Yamamoto, & Mimura, ; Goto et al, ; Kiminami, ; Kiminami & Ishihama, ; Kiminami & Toda, ; Utsunomiya et al, ; Zaw Win Ko et al, ; Enami, unpublished data) of the Sanbagawa metamorphic belt. Mfc, mafic clot; Qpd, quartz‐poor domain; Qrd, quartz‐rich domain in quartz eclogite (GE1501a) shown in Figure .…”
Section: Chemical Compositions Of Quartz Eclogitementioning
confidence: 94%
“…Speculated subduction-boundary geotherm at about 89 Ma Figs. 2b, 2d Ds Wallis, 1990Hara et al, 1992Wallis et al, 1992;Aoya, 2002;Mizukami and Wallis, 2005;Mori and Wallis, 2010 -3 Wallis and Ar-Ar Itaya and Takasugi, 1988;Takasu and Dallmeyer, 1990;Dallmeyer and Takasu, 1991;Itaya and Fukui, 1994 -91- Kabir and Takasu (2011) (for Seba pelite in SB), Endo and Tsuboi (2013) (for EI) and Weller et al (2015) (for SB and Kotsu). For Ota et al (2004), only P-T estimates obtained from mineral assemblages involving garnet, clinopyroxene and phengite are plotted.…”
Section: Fettes and Desmons 2007mentioning
confidence: 99%
“…Abbreviations of rock-body names other than KT (Kotsu) follow Fig.3. Petrologically derived P-T paths (Mizukami & Wallis (2005) for HA, Endo (2010) and Endo et al (2012) for WI, Aoya et al (2003) and Weller et al (2015) for KT, and Enami (1998) for the Shirataki unit are shown by bold arrows, and those derived using thermal model of Endo et al (2012) by dashed bold arrows. (a) 117-109 Ma.…”
Section: Fettes and Desmons 2007mentioning
confidence: 99%